2020
DOI: 10.1002/ijgo.13089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral hyoscine used for outpatient cervical ripening among primiparous women with term pregnancy

Abstract: Objective: To assess the efficacy and safety of outpatient administration of oral hyoscine for cervical ripening. Methods: In a randomized controlled trial at a university hospital in Tehran between September 2017 and December 2018, 100 primiparous women with singleton pregnancy at 38 0-40 0 gestational weeks and Bishop score of 5 or less were randomized to either routine expectant management (control group) or 10 mg of oral hyoscine twice daily for 1 week, followed by once daily for 1 week (hyoscine group). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
4
6
0
1
Order By: Relevance
“…It overcomes cervical spasm by its selective blocking action on the intramural parasympathetic ganglia of the cervico-uterine plexus, thus aids cervical dilatation without affecting uterine contractions. 9,17,20 This mechanism of action of hyoscine explains its effectiveness on cervical ripening as obtained in this study, duration of first stage of labour 9 , abortion process 19 , and intrauterine procedures. 21 The clinical significance of the shorter cervical ripening time obtained in this study with combined vaginal misoprostol and intramuscular hyoscine, is that this combination may be more suitable for clinical conditions where there is need to ripen the cervix faster and expedite delivery before induction of labour.…”
Section: Discussionsupporting
confidence: 62%
“…It overcomes cervical spasm by its selective blocking action on the intramural parasympathetic ganglia of the cervico-uterine plexus, thus aids cervical dilatation without affecting uterine contractions. 9,17,20 This mechanism of action of hyoscine explains its effectiveness on cervical ripening as obtained in this study, duration of first stage of labour 9 , abortion process 19 , and intrauterine procedures. 21 The clinical significance of the shorter cervical ripening time obtained in this study with combined vaginal misoprostol and intramuscular hyoscine, is that this combination may be more suitable for clinical conditions where there is need to ripen the cervix faster and expedite delivery before induction of labour.…”
Section: Discussionsupporting
confidence: 62%
“…CR has many positive outcomes and prevents perinatal injuries such as severe perineal injuries (7). Contrarily, poor CR is associated with many different adverse consequences such as prolonged labor, fetal distress, excessive bleeding, infection, and increased need for medical interventions such as Cesarean section, particularly among primiparous women (2,8,9). Therefore, interventions for CR before labor induction are common to facilitate successful childbirth (10).…”
Section: Introductionmentioning
confidence: 99%
“…I have read the interesting study by Naeiji et al 1 about using oral hyoscine for outpatient cervical ripening. Nearly 84% of pregnant women who undergo induction of labor require cervical ripening 2 ; this should be safe and cost‐effective.…”
mentioning
confidence: 99%
“…Naeiji et al 1 conducted a clinical trial to assess the efficacy and safety of outpatient administration of oral hyoscine for cervical ripening. The authors concluded that oral hyoscine in an outpatient setting was found to ripen the cervix with no significant adverse drug reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation